Phase Variable Expression of a Single Phage Receptor in Campylobacter jejuni NCTC12662 Influences Sensitivity Toward Several Diverse CPS-Dependent Phages - Gencay, Yilmaz Emre; Sørensen, Martine C. H.; Wenzel, Cory Q.; Szymanski, Christine M.; Brøndsted, Lone (Frontiers in Microbiology, 2018)
Campylobacter jejuni NCTC12662 is sensitive to infection by many Campylobacter bacteriophages. Here we used this strain to investigate the molecular mechanism behind phage resistance development when exposed to a single phage and demonstrate how phase variable expression of one surface component influences phage sensitivity against many diverse C. jejuni phages. When C. jejuni NCTC12662 was exposed to phage F207 overnight, 25% of the bacterial cells were able to grow on a lawn of phage F207, suggesting that resistance develops at a high frequency. One resistant variant, 12662R, was further characterized and shown to be an adsorption mutant. Plaque assays using our large phage collection showed that seven out of 36 diverse capsular polysaccharide (CPS)-dependent phages could not infect 12662R, whereas the remaining phages formed plaques on 12662R with reduced efficiencies. Analysis of the CPS composition of 12662R by high-resolution magic angle spinning nuclear magnetic resonance (HR-MAS NMR) showed a diminished signal for O-methyl phosphoramidate (MeOPN), a phase variable modification of the CPS. This suggested that the majority of the 12662R population did not express this phase variable modification in the CPS, indicating that MeOPN serves as a phage receptor in NCTC12662. Whole genome analysis of 12662R showed a switch in the length of the phase variable homopolymeric G tract of gene 06810, encoding a putative MeOPN-transferase located in the CPS locus, resulting in a non-functional protein. To confirm the role of 06810 in phage resistance development of NCTC12662, a 06810 knockout mutant in NCTC12662 was constructed and analyzed by HR-MAS NMR demonstrating the absence of MeOPN in the CPS of the mutant. Plaque assays using NCTC12662 06810 deletion mutant demonstrated that seven of our CPS-dependent Campylobacter phages are dependent on the presence of MeOPN for successful infection of C. jejuni, whereas the remaining 29 phages infect independently of MeOPN, although with reduced efficiencies. Our data indicate that CPS-dependent phages uses diverse mechanisms for their initial interaction with their C. jejuni host.